Spiritual Education as a Catalyst for Quality Learning: Empirical Evidence from Madrasahs - Badrudin Badrudin; Juhji Juhji; Waesul Kurni (Nazhruna: Jurnal Pendidikan Islam, 2025)
Improving the quality of education in madrasahs (Islamic schools) remains a concern, as these institutions strive to balance the development of spiritual values and professional proficiency with supportive learning environments. This study addresses ongoing debates about the quantifiable effects of faith-based pedagogy by examining how spiritual education, teacher professionalism, and school atmosphere influence educational quality. A quantitative design was employed involving 312 purposively selected madrasah teachers, and data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4. The findings show that while the impact of spiritual education (β = 0.008) is statistically insignificant, the school environment (β = 0.568) and teacher professionalism (β = 0.318) considerably improve educational quality. These results highlight the importance of promoting professional competence and a supportive institutional environment to enhance madrasah performance. Meanwhile, the limited impact of spiritual education suggests the need for a more pedagogically grounded, evidence-based integration of spiritual values into instructional practices.